Multi-parameter sensing with a single magnetoelastic sensor by applying loads on the null locations of multiple resonant modes. (23rd February 2016) - DeRouin, Andrew; Ong, Keat Ghee
Abstract: Magnetoelastic sensors are mass sensitive sensors commonly used for stress and pressure measurement, as well as chemical and biological monitoring when combined with a functionalized coating. Magnetoelastic sensors are typically made of free-standing, rectangular strips of magnetoelastic materials that exhibit longitudinal, extensional vibrations due to the excitation of magnetic fields. A single magnetoelastic sensor is generally used to monitor one parameter since only the fundamental resonant frequency is measured. Multiple-parameter sensing in close proximity has previously been achieved by using multiple magnetoelastic sensors of different dimensions and tracking their resonant frequencies independently. However, this requires a large surface area and inconvenient layout of dissimilarly shaped sensors. This paper presents a technique for monitoring multiple parameters with a single magnetoelastic sensor by applying separate mass loads at the null points (points of zero vibration) of multiple resonant modes. Applying a load at a null location does not affect the corresponding resonant mode but alters the resonant frequencies of other modes. Therefore, by isolating the variables of interest to multiple null points and simultaneously measuring the resonant frequency shifts of related resonant modes, the masses at each null location can be calculated. Results showed that changing the coverage at a null location along the width of the sensor can be used to minimize the loading effect on the corresponding resonant mode. In contrast, changing the lengthwise coverage can maximize the loading effect on other resonant modes, thus increasing the mass sensitivity of the sensor. Furthermore, simultaneously applying loads to null points of multiple resonant modes had a nearly additive effect, allowing detection of multiple parameters with a single magnetoelastic sensor.